Characteristic Study of Butterfly Pea Flower and Some of Its Products: Review - Pradip K. Wankhade; Krishna Gaurkhede; Shravani Dudhe (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In Asia tropic mostly native herbal medicinal plant Butterfly Pea (Clitoria ternatea) found which is generally used for to enhance the memory and anxiolytic agent. In different parts of the plant various constituents are found. Antibacterial, antioxidant, anti-inflammatory, cytotoxic and antidiabetic are found in activities in flower extract which is advantageous to human being health. These flowers are due to its therapeutic properties can also be useful for food because of its unharmful, health benefits and efficacy. Tannins, resins, starch, taraxerol, taraxerone, alkaloids, flavonoids, saponins, proteins, anthocyanins and carbohydrates are the active chemical constituents from this plant. In traditional medicine, the plant extract can be used in treatment of jaundice, migraine, throat, eye infections, skin disease, asthma, swollen joints, ear-ache, eruptions, fever, urinary tract infections, constipations, snake-bites, head-ache, indigestion, leprosy and central nervous system disorders. Its various extracts having the usefulness in various pharmacological activities such as sedative, anti-pyretic, anti-inflammatory, anti-diabetic, anti-oxidative, anti-stress, and anti-microbial and memory enhancing. Hence, this review is an effort to get exhaustive literature survey of the on its pharmacognosy, phytochemistry, and its traditional uses along with special emphasis given on pharmacological activities and its use in food and drinks.
Keywords: herbal; antioxidant; antibacterial; traditional medicine; food colour